Wintertime weather‐climate variability and its links to early spring ice‐out in Maine lakes. (4th September 2015) - Beyene, Mussie T.; Jain, Shaleen
Abstract: In recent decades, Maine lakes have recorded their earliest ice‐out dates in over a century. In temperate regions, seasonal lake ice‐cover is a critical phenomenon linking climate, aquatic ecosystem and society. And the lengthening of the ice‐free period due to warmer climate has been linked to increased algal growth and declining lake water quality, warming of water temperatures leading to alterations in aquatic biodiversity, and the shortening of ice‐fishing period and other traditional winter activities over lakes. In this study, historical record of eight lakes and six benchmarked meteorological stations in Maine for the period 1950–2010 were analyzed to (1) investigate the relationship between antecedent winter (January–February) temperatures, degree‐day variables, and spring‐time ice breakup dates, including the identification of thresholds and (2) determine the influence of the extreme phases of select atmospheric teleconnection patterns (Tropical Northern hemisphere‐ TNH and North Atlantic Oscillation‐ NAO) on the winter degree‐day quantities and spring ice‐out dates. The influence of antecedent winter degree‐days on spring ice‐out dates was characterized by determining the threshold winter accumulated freezing and melting degree‐day (AFDD and AMDD), the exceedance (non‐exceedance) of which engenders early (late) spring ice‐out dates. Statistical analysis between teleconnection indices and winter AFDD and/or AMDD quantities for Maine revealed an asymmetric relationship. Strongly negative phases of TNH and, to a lesser extent, positive phases of NAO are linked with spatial and temporal pattern of early spring ice breakup events in Maine lakes. These relationships taken together with observed warming trends have the potential to accelerate the decline in water quality in Maine lakes.